The presence of the Problem-based Learning syntax in junior high school biology textbooks - Nurdiyah Lestari; St Muthmainnah Yusuf; K. Ivo Basri; S. Suciati; Mohammad Masykuri (University of Muhammadiyah Malang, 2020)
Learning resources and learning models are the two main components that determine learning success. Of the many learning models, Problem-based Learning (PBL) is one of the most recommended in biology learning. The purpose of this content analysis was to identify the emergence of PBL syntax in junior high school biology textbooks. The population in this study were all biology textbooks for the VII graders, while the sample was three biology textbooks that are often used by VII graders in Surakarta. As the results, the averages of each PBL step emerged in the textbooks analyzed i.e. problem-oriented activity, organizing to collect data, assisting independent investigations, artifacts presentations, and analyzed/evaluated the process of overcoming the problem were 17%, 47%, 23%, 2%, and 11%, respectively. Thus, it can be concluded that the biology textbooks analyzed have applied PBL learning models, yet the proportion between steps is not balanced.